Ambient temperature and risk of cardiovascular and respiratory adverse health outcomes: a nationwide cross-sectional study from Spain - Achebak, Hicham; Rey, Grégoire; Lloyd, Simon J; Quijal-Zamorano, Marcos; Méndez-Turrubiates, Raúl Fernando; Ballester, Joan (European journal of preventive cardiology, 2024)
Abstract Aims We assessed the association of temperature and temperature variability with cause-specific emergency hospitalizations and mortality from cardiovascular and respiratory diseases in Spain, as well as the effect modification of this association by individual and contextual factors. Methods and results We collected data on health (hospital admissions and mortality), weather (temperature and relative humidity), and relevant contextual indicators for 48 Spanish provinces during 2004–2019. The statistical analysis was separately performed for the summer (June–September) and winter (December–March) seasons. We first applied a generalized linear regression model with quasi-Poisson distribution to estimate daily province-specific temperature-health associations, and then we fitted multilevel multivariate meta-regression models to the evaluate effect modification of the contextual characteristics on heat- and cold-related risks. High temperature increased the risk of mortality across all cardiovascular and respiratory diseases, with the strongest effect for hypertension (relative risk (RR) at 99th temperature percentile vs. optimum temperature: 1.510 [95% empirical confidence interval {eCI} 1.251 to 1.821]), heart failure (1.528 [1.353 to 1.725]), and pneumonia (2.224 [1.685 to 2.936]). Heat also had an impact on all respiratory hospitalization causes (except asthma), with similar risks between pneumonia (1.288 [1.240 to 1.339]), acute bronchitis and bronchiolitis (1.307 [1.219 to 1.402]), and chronic obstructive pulmonary disease (1.260 [1.158 to 1.372]). We generally found significant risks related to low temperature for all cardiovascular and respiratory causes, with heart failure (RR at 1st temperature percentile vs. optimum temperature: 1.537 [1.329 to 1.779]) and chronic obstructive pulmonary disease (1.885 [1.646 to 2.159]) exhibiting the greatest risk for hospitalization, and acute myocardial infarction (1.860 [1.546 to 2.238]) and pneumonia (1.734 [1.219 to 2.468]) for mortality. Women and the elderly were more vulnerable to heat, while people with secondary education were less susceptible to cold compared to those not achieving this educational stage. Results from meta-regression showed that increasing heating access to the highest current provincial value (i.e. 95.6%) could reduce deaths due to cold by 59.5% (57.2 to 63.5). Conclusion Exposure to low and high temperatures was associated with a greater risk of morbidity and mortality from multiple cardiovascular and respiratory conditions, and heating was the most effective societal adaptive measure to reduce cold-related mortality. Lay Summary Exposure to low and high temperatures increases the risk of morbidity and mortality from several cardiovascular and respiratory diseases, especially among the elderly. Increasing access to heating could substantially reduce cold-related mortality burden.